COMMUNITY SERVICE OPTIMIZING MENTAL SELF-CARE FOR PREGNANT WOMEN THROUGH JAVANESE TRADITIONS IN MEDICAL MODIFICATION AT THE DELIMA CLINIC - Ruminta Sirait; Siska M.O Napitupulu; Septiani Kusumas Tutik (Jurnal Masyarakat Indonesia (Jumas), 2024)
Pregnancy is a crucial transitional phase that involves significant physical changes and complex psychological changes. Unstable emotional conditions during pregnancy can trigger antenatal depression which adversely affects maternal health and fetal development. This community service activity aims to increase the understanding and ability of pregnant women regarding the importance of self-care (self-care mental) by utilizing medically modified Javanese traditions. The activity was carried out at the Medan Pomegranate Clinic by the academic team from STIKes Darmo Medan. The method used is interactive health counseling to pregnant women and families, and is evaluated through a pre-test and post-test quantitative design. The results of the activity showed a significant increase in participants' understanding of the management of psychological conditions, reduction of anxiety levels, and filtering of the noble values of tradition to be in harmony with safe medical principles. The main supporting factor is the high enthusiasm of the participants, while the inhibiting factor is the still strong belief in certain local myths that trigger anxiety. In conclusion, the integration of local traditions and medical standards is able to become an effective holistic antenatal care model to reduce stress rates in pregnant women.